Control interno y su relación con la gestión administrativa en la empresa industrial Gema S.A. ciudad de Chimbote, 2018 - Urrutia Mendez, Milagros karin (2020)
ABSTRACT The purpose of the present investigation is determining the relationship between internal control and administrative management in the industrial company Gema S.A. Chimbote city. The study was non-experimental and the descriptive - correlational design. In the present investigation, 10 workers in the audit area were selected through simple random sampling, a reliable and validated questionnaire was used to collect the field information; The data obtained were processed through the SPS statistics software. It is concluded that internal control is positively related to administrative management; According to the Shapiro-Wilk test contingency coefficient, the value is τ = 0.865, with a significance level of less than 5% of standard significance (P <0.005) and a Pearson correlation coefficient. It is recommended that the audit manager of the company Gema S. A. should perform a diagnosis and evaluation of the internal control team to make the necessary changes and develop an induction on the processes that the internal control complies in order to determine a good administrative management.